Inclusive Education and the Protection of Children’s Rights within an Islamic Educational Framework - Fajriah Inayati; Fitri Aulia; Ariska, Mutiara; Sulaiman, Ahmad Ismail (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2025)
This study aims to examine the concept of inclusive education from the perspective of Islamic education in promoting a non-discriminatory educational system. The research adopts a library-based methodology, analyzing 25 sources comprising textbooks, peer-reviewed academic journals, and relevant legal and policy documents. The scope of the study encompasses the historical development of inclusive education, its guiding principles of implementation, and the theological foundations of children’s rights within Islamic teachings. The findings indicate that inclusive education is congruent with core Islamic values of equality and justice, as articulated in Surah Al-Hujurat (49:13), which emphasizes that human dignity is determined by piety rather than physical or social attributes. Although Indonesia has established a relatively comprehensive regulatory framework supporting inclusive education, its implementation remains constrained by several factors, including limited teacher competence, inadequate infrastructure, and insufficient institutional understanding. These findings underscore that the principles of “diversity as a strength” and the adoption of adaptive curricula represent practical manifestations of holistic Islamic education. Furthermore, synergetic collaboration among government institutions, educational providers, and the wider community is essential for fostering an equitable learning environment. Effective implementation ultimately requires strong teacher commitment to adaptive and responsive pedagogical practices to ensure that the potential of all learners, including children with special needs, is optimally developed in accordance with their individual capacities. Abstrak: Penelitian ini bertujuan untuk mengkaji konsep pendidikan inklusif dalam perspektif pendidikan Islam guna mewujudkan sistem pendidikan yang non-diskriminatif. Metode penelitian yang digunakan adalah studi pustaka (library research) dengan menganalisis 25 referensi yang terdiri dari buku teks, jurnal ilmiah, dan peraturan perundangan terkait. Fokus kajian meliputi sejarah, prinsip pelaksanaan, serta landasan teologis hak anak. Hasil penelitian menunjukkan bahwa pendidikan inklusif selaras dengan nilai fundamental Islam mengenai kesetaraan dan keadilan, sebagaimana ditegaskan dalam QS. Al-Hujurat: 13 bahwa kemuliaan manusia terletak pada ketakwaannya, bukan kondisi fisik. Meskipun secara regulasi di Indonesia sudah kuat, implementasinya masih terhambat oleh keterbatasan kompetensi guru, sarana prasarana, dan pemahaman sekolah. Temuan ini menekankan bahwa prinsip keragaman sebagai kekuatan dan kurikulum adaptif merupakan manifestasi pendidikan Islam yang holistik. Diperlukan kolaborasi sinergis antara pemerintah, sekolah, dan masyarakat untuk menciptakan lingkungan belajar yang adil. Implementasi yang efektif menuntut komitmen guru dalam pembelajaran adaptif agar potensi setiap peserta didik, termasuk Anak Berkebutuhan Khusus (ABK), dapat berkembang optimal sesuai kemampuan masing-masing.